2017
DOI: 10.1002/jcop.21917
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood sexual violence moderates women's perceived safety in urban neighborhoods

Abstract: Perceptions of neighborhood safety are positively associated with perceptions of neighborhood violence. However, research has yet to examine whether this relationship is moderated by specific types of violence, such as sexual violence, that are more salient for women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The police do not take part in interdicting the launch of missiles or posing obstacles in their way, however they are the first responders and hold overall responsibility for handling the scenes of missile landings; their bomb treat the remains of the missiles; and Police Officers are responsible for directing traffic and crowds around the scene and assisting local residents. In the latest study done in American urban cities, some of the perceived violence includes rape, assault, fighting with weapons, gang fights and robberies or muggings (Hoffman, Mair, Hunter, Prince & Tebes, 2018). The research findings are that men and women in the high crime urban cities did not have any difference in the way they perceived safety and violence which was around them.…”
mentioning
confidence: 75%
“…The police do not take part in interdicting the launch of missiles or posing obstacles in their way, however they are the first responders and hold overall responsibility for handling the scenes of missile landings; their bomb treat the remains of the missiles; and Police Officers are responsible for directing traffic and crowds around the scene and assisting local residents. In the latest study done in American urban cities, some of the perceived violence includes rape, assault, fighting with weapons, gang fights and robberies or muggings (Hoffman, Mair, Hunter, Prince & Tebes, 2018). The research findings are that men and women in the high crime urban cities did not have any difference in the way they perceived safety and violence which was around them.…”
mentioning
confidence: 75%
“…In an Australian sample, women reported an average of one encounter of stranger harassment every 2 days over a 7-day period (Holland, Koval, Stratemeyer, Thomson, & Haslam, 2017). These objectively high rates of sexual violence and harassment against women may explain why women consistently report greater threats to physical safety than men do (Harris & Miller, 2000; Hoffman, Mair, Hunter, Prince, & Tebes, 2018).…”
Section: Gender Sexual Violence and Stranger Harassmentmentioning
confidence: 99%
“…Since this item refers to the subjective well‐being, the present result supports the studies of Bedin and Sarriera (2015) and Santos, Sarriera, and Bedin (2018) who also found significant differences for sex, with Brazilian adolescent boys presenting higher averages of subjective well‐being than girls, being the last one in a more vulnerable place. Although conducted with adults, a study found that women's perceptions of neighborhood sexual violence predicted perceived safety in their neighborhood, but men's did not, illustrating the importance of taking gender and perceived sexual violence into account to understand neighborhood safety (Hoffman, Mair, Hunter, Prince, & Tebes, 2017).…”
Section: Discussionmentioning
confidence: 99%